2018
DOI: 10.1016/j.ecss.2018.02.027
|View full text |Cite
|
Sign up to set email alerts
|

Terrestrial laser scanning to quantify above-ground biomass of structurally complex coastal wetland vegetation

Abstract: Above-ground biomass represents a small yet significant contributor to carbon storage in coastal wetlands. Despite this, above-ground biomass is often poorly quantified, particularly in areas where vegetation structure is complex. Traditional methods for providing accurate estimates involve harvesting vegetation to develop mangrove allometric equations and quantify saltmarsh biomass in quadrats. However broad scale application of these methods may not capture structural variability in vegetation resulting in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 57 publications
1
23
0
Order By: Relevance
“…The last four LiDAR metrics include two metrics describing the point cloud variation (HVAR and HSD), one density metric (D01), and one canopy cover index (CC 1.3 ). The sensitivity of the HVAR and HSD in this study are in accordance with what was observed by Owers et al [40] in a mangrove AGB study using terrestrial LiDAR. Consequently, we can infer that the canopy thickness is the most important LiDAR metric for mangrove AGB estimation, followed by upper canopy height metrics, bottom canopy height metrics, and point cloud variation metrics, in that order.…”
Section: Relevance Of Predictor Variablessupporting
confidence: 92%
See 1 more Smart Citation
“…The last four LiDAR metrics include two metrics describing the point cloud variation (HVAR and HSD), one density metric (D01), and one canopy cover index (CC 1.3 ). The sensitivity of the HVAR and HSD in this study are in accordance with what was observed by Owers et al [40] in a mangrove AGB study using terrestrial LiDAR. Consequently, we can infer that the canopy thickness is the most important LiDAR metric for mangrove AGB estimation, followed by upper canopy height metrics, bottom canopy height metrics, and point cloud variation metrics, in that order.…”
Section: Relevance Of Predictor Variablessupporting
confidence: 92%
“…Few studies have used high-density LiDAR point clouds to estimate mangrove AGB, and few studies have reported the most important LiDAR metrics for predicting mangrove AGB [13,14]. A total of 53 LiDAR metrics were derived preliminarily (24 for height, 12 for density, and 17 for canopy volume) [14,37], as presented in Table A1 [14,[38][39][40]. A novel canopy thickness metric (CTHK) was created and used to describe the thickness of mangrove canopy based on the analysis of UAV-LiDAR point clouds [41].…”
Section: Lidar Metrics and Sentinel-2 Indicesmentioning
confidence: 99%
“…Consequently, carbon financing and accounting methods recommend and reward the use of accurate, site-based measurements of mangrove above-and below-ground carbon pools that capture variability and improve confidence in carbon stock estimates (Gibbs et al, 2007;Kauffman and Donato, 2012;Howard et al, 2014;IPCC, 2014). However, the mangrove above-ground carbon pool is generally poorly quantified (Owers et al, 2018b).…”
Section: Introductionmentioning
confidence: 99%
“…A volumetric or surface differencing approach was used to estimate mangrove forest volume, which involves subtracting a DTM from a DSM to obtain a CHM, thereby normalizing object heights above ground [52]. Forest volume, which includes all pixels associated with aboveground vegetation, can then be estimated by multiplying the canopy height value of a raster cell by its resolution [53,54]. A DTM was created in ArcMap (version 10.6) by interpolating all 45 topographic points with the 'Topo to Raster' tool ( Figure 5).…”
Section: Volume Calculationmentioning
confidence: 99%